Assessing the Proportionality of Criminal Sanctions Imposed on Notaries and Land Deed Officials (PPAT) in Document Forgery Cases - Hafid, Saiful Harun Alhakim; Sihombing, B.F. (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The growing complexity of document forgery and money laundering cases involving notaries and Land Deed Officials (PPAT) has raised serious concerns regarding the boundaries of criminal liability for public officials. This study aims to identify and assess the criminal liability of notaries and PPATs and to analyze the alignment of criminal sanctions with the principles of justice, legal certainty, and the objectives of criminal punishment, as reflected in the West Jakarta District Court Decision No. 248/Pid.B/2022/PN.Jkt.Brt. The research employs a normative juridical approach, utilizing case-based, conceptual, and statutory analyses. The findings reveal that the criminal liability of notaries and PPATs remains uncertain, particularly in establishing elements of culpability and ensuring the proportionality of sanctions. In conclusion, while law enforcement in this case has achieved legal certainty, it has not yet fully realized substantive justice or the restorative justice objectives of punishment.